Konstruksi Identitas Komunitas Arab Hadrami di Yayasan Pergururan Islam Adabiyah - Shania Shania; Linda Linda; Larissa Putri Isyara; Maryamah Maryamah; Fitri Oviyanti (Instructional Development Journal, 2024)
This research aims to explore the construction of the Arab Hadrami community's identity at the Adabiyah Islamic Education Foundation, focusing on the rituals practiced and their impact on shaping students' character. The research method used is a qualitative approach with data collection instruments including in-depth interviews, observation, and documentation. The research results indicate that the efforts made by the Islamic Education Foundation in instilling the values and character that are characteristic of the Arab Hadrami community involve constructing several Alawiyyin rituals. Therefore, the Arab Hadrami community at the Islamic Education Foundation constructs its identity through three processes: externalization, objectification, and internalization. Externalization, as a form of transmitting Alawiyyin ancestral culture at the Adabiyah Islamic Education Foundation, is realized through the implementation of several rituals related to the Alawiyyin order, such as the recitation of wirid, poetry, shalawat, and other practices that are an integral part of the institution. These rituals are objectified, containing values such as knowledge, practice, wirid, and morality, which are internalized into the daily learning activities that strengthen students' identity as part of the Arab Hadrami community and shape their character based on the Islamic and moral values taught by the traditions of the Arab Hadrami community at the Adabiyah Islamic Education Foundation.